Presepsi Ibu Tentang Asuhan Balita Oleh Mahasiswa Tingkat III Dalam Program Mitra Keluarga - Ranti Febriyani; Sri Astuti; R. Tina Dewi Judistiani; Sefita Aryuti Nirmala (AIPKIND (Asosiasi Pendidikan Kebidanan Indonesia), 2019)
Sustainable midwifery services, focusing on the aspects of prevention, health promotion and empowerment based on partnerships with the community. The role and function of the midwives of which gives the orphanage on toddlers. The purpose of this research is to know the presepsi of satisfaction towards the care of mothers on toddlers given student level III as a partner of the family. Our satisfaction patients based on reliability, responsiveness, assurance, empathy and physical evidence. This research is quantitative research descriptive research method with the pontong approach of latitude, the population in this research is to foster family found a toddler in the village of Cikeruh and the villages of Cipacing, sampling in the This research uses the technique of total sampling samples used are 46 mother foster family. Data collection is done using primary data and distribute questionnaires.The Research results obtained from 46 mother of our satisfaction in giving care is 52.2% 47.8% feel satisfied and not satisfied against the care given to toddlers. Based on the characteristics of mothers with primary education being satisfied as much as 53.8%, 20-35-year-old mother was satisfied 83.3% and mothers who are not working as much satisfied 95.8%. Our satisfaction about the physical evidence 60.9% were satisfied and about the response of 58.7% were satisfied, regarding the reliability of 58.7% were satisfied, about empathy 52.2% were satisfied and about 52.2% satisfied guarantee. Conclusions on the research of family foster mother that our satisfaction satisfied against the orphanage toddler as much as 52.2%. That's already been given appropriate and expected by the mother.